Effect of Teachers Problems in Using Digital Resources on Mathematical Content Instruction Online - Joshi, Dirgha Raj; Sharma Chapai, Krishna Prasad; Khanal, Bishnu (International Research Journal of MMC, 2023)
The aim of the research was to find the effect of the problems of mathematics teachers in teaching mathematics online on instructing mathematical content. A cross-sectional online survey design was employed among 258 secondary-level mathematics teachers in Nepal. ADD Path analysis model under structural equation modeling was the major statistical technique used in the research. The finding indicates that the problems of mathematics teachers in internet surfing, class control, interest in online courses, and digital content development are major contributing factors to instructing mathematical content online.